Learning algorithm concepts by developing them in educational gameplay: From the perspective of college students in Perak - Siti Sakinah Mohd Yusof; Azniah Ismail; Nor Azah Abdul Aziz (Pejabat Karang Mengarang UPSI, 2022)
The purpose of this study was to determine whether the game developer tool has good capabilities to assist students in learning algorithm concepts and determine whether the game developer tool promotes a good student attitude. This research is based on a descriptive study design involving only one single sample. Quantitative data was collected through a questionnaire. The questionnaire is divided into 3 sections which are demographic information, tool capability, and student attitude. There are a total of 78 students from two modules (Physics and Biology), who took part in this research. The highest score for the tool capability section is "Scratch 3.0 help me achieve my objective to develop the educational game" while the highest score for the student attitude section is "I enjoy learning using Scratch 3.0". It is proven that learning algorithm concepts by developing them in educational gameplay help students to learn in an enjoyable environment.